Demons of Urban Reform - Stokes, Laura Patricia. author. aut Link
VII, 235 p.
Keywords: A comparative analysis of early witch trials in Lucerne, Nuremberg and Basel, within the context of criminal justice and social control. The case of Lucerne presents a fascinating interplay between witch trials and a transformation in the city's criminal procedure on one hand, and between witchcraft fears and social control on the other.